1991
DOI: 10.1016/0006-2952(91)90442-8
|View full text |Cite
|
Sign up to set email alerts
|

Reduced responsiveness of adenylate cyclase to forskolin in human lymphoma cells

Abstract: Abstract-The

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Recently, we have demonstrated that the function of the b 2 -AR complex is altered in low-grade non-Hodgkin's lymphomas (NHL). In particular, the cellular production of cAMP was decreased in mononuclear leucocytes (MNLs) from NHL patients [14]. This study extends these earlier observations and demonstrates that the impairment of the b 2 -AR complex in MNLs of CLL patients is correlated with disease progression, suggesting that a reduced cAMP production in response to specific external stimuli may be involved in disease progression of CLL.…”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations
“…Recently, we have demonstrated that the function of the b 2 -AR complex is altered in low-grade non-Hodgkin's lymphomas (NHL). In particular, the cellular production of cAMP was decreased in mononuclear leucocytes (MNLs) from NHL patients [14]. This study extends these earlier observations and demonstrates that the impairment of the b 2 -AR complex in MNLs of CLL patients is correlated with disease progression, suggesting that a reduced cAMP production in response to specific external stimuli may be involved in disease progression of CLL.…”
Section: Introductionsupporting
confidence: 84%
“…In low-grade non-Hodkgin's lymphoma and in various other human malignancies, decreased cAMP levels were observed [13,26,27]. This is reflected by reduced numbers of b 2 -adrenergic receptors and a reduced cAMP production in response to catecholamine stimulation [14][15][16][17]. This is reflected by reduced numbers of b 2 -adrenergic receptors and a reduced cAMP production in response to catecholamine stimulation [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In human lymphoma cells, there was a reduced response of beta-adrenergic receptors, also the authors indicated a reduction of protein G s and a reduction in the response to forskolin [17]. In lymphocytes of depressed patients, we found that there was a significant difference in the stimulation of adenylate cyclase by forskolin, which was reduced in the patients.…”
Section: Discussionmentioning
confidence: 81%